2015
DOI: 10.1117/12.2189655
|View full text |Cite
|
Sign up to set email alerts
|

Coded multi-angular illumination for Fourier ptychography based on Hadamard codes

Abstract: Fourier ptychographic microscopy (FPM) is a newly developed super-resolution technique, which employs angularly varying illumination and a phase retrieval algorithm to surpass the diffraction limit of the objective lens. Specifically, FP captures a set of low-resolution (LR) images, under angularly varying illuminations, and stitches them together in the Fourier domain. However, because the requisite large number of incident illumination angles, the long capturing process becomes an obvious limiting factor. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…By illuminating multiple LEDs at a time for each captured image, it was shown that the incoherent superposition of the contribution of each LED could be separated within a novel reconstruction algorithm. After this demonstration, several strategies were proposed to choose alternative multiplexing LED patterns [128][129][130][131][132], and similar approaches were also later suggested for spectral multiplexing [79,133]. One of the fastest FP systems to date was demonstrated using this multiplexing concept [26].…”
Section: High-speed Fourier Ptychographymentioning
confidence: 99%
“…By illuminating multiple LEDs at a time for each captured image, it was shown that the incoherent superposition of the contribution of each LED could be separated within a novel reconstruction algorithm. After this demonstration, several strategies were proposed to choose alternative multiplexing LED patterns [128][129][130][131][132], and similar approaches were also later suggested for spectral multiplexing [79,133]. One of the fastest FP systems to date was demonstrated using this multiplexing concept [26].…”
Section: High-speed Fourier Ptychographymentioning
confidence: 99%
“…Fourier ptychography imaging draws on the idea of synthetic aperture [1] , using LED arrays of different positions for imaging. Acquiring multiple low-resolution images containing different spectrum components, Fourier ptychography use the phase recovery technology, and finally obtains a high-resolution, large field of view imaging results [2][3][4][5][6][7][8] . The phase recovery process is essentially an inverse problem solved optimally.…”
Section: Introductionmentioning
confidence: 99%
“…The final reconstruction resolution is determined by the sum of the objective lens and illumination NAs [20]. In order to exceed the limitations of the original FPM technique, several studies have been reported to further improve FPM and FP [21][22][23][24][25][26][27][28] lately. Some of them correct the system aberrations of FPM and improve its reconstruction accuracy and recovery resolution significantly [21,22,24,28].…”
mentioning
confidence: 99%
“…Some of them correct the system aberrations of FPM and improve its reconstruction accuracy and recovery resolution significantly [21,22,24,28]. The others reduce the measuring time of FPM imaging process and remarkably improve its data acquisition efficiency [23][24][25][26][27]. However, similar to conventional ptychography, FP suffers from a positional misalignment problem, which is rarely mentioned in those developed FP techniques.…”
mentioning
confidence: 99%